NONINVASIVE NASAL MUCOSA EXPOSURE TO TREAT AND PREVENT RHINITIS AND RHINOSINUSITIS OF VARIOUS GENESIS - E. Yu. Radtsig; L. A. Babakina; M. R. Bogomilsky (Klinicist)
The paper deals with the evaluation of the nasal mucosa in health and in different abnormalities. It describes the possibilities of using drugs of different groups to relieve symptoms in nasal mucosal and paranasal sinus abnormalities of different genesis, as well as the preventive effect of some of these drugs.